Lyrik und Erkenntnis. Einleitende Überlegungen - Ralph Müller (Universität Trier, 2019)
The relationship between poetry and cognition appears, at first glance, as hardly compelling as that of art and science, of feeling and thinking, or even of intuition and analysis. For this reason, its analysis is fundamentally concerned with questions from philosophical and literary criticism perspectives: Which forms of “cognition” are possible in poetry? In what way and in what forms can poetry also be a medium of generation and/or mediation of cognition, experience or even knowledge and truth? And which processes, matters, or “information” are thereby privileged? Are there subgenres of poetry, for example historical poetry, reflective poetry or didactic poetry, that are especially relevant as regards cognitive functions? And can cognition also be mediated through aura, Stimmung or experience?